STRATEGI MANAJEMEN MUTU DALAM MEMBANGUN HUBUNGAN SALING MENGUNTUNGKAN ANTARA SEKOLAH DAN KANTIN SEKOLAH - Shofiyyah, Alya; Gede Dian Puspita, Ni Luh; Weki Sera, Salvator Ronaldo; Azainil (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to identify quality strategies in building mutually beneficial relationships between schools and school canteens. The research method used is a case study with qualitative analysis. The results of the study indicate that effective quality strategies in building mutually beneficial relationships between schools and school canteens include: Effective communication: Schools and school canteens must have effective communication to understand each other's needs and expectations. Good cooperation: Schools and school canteens must have good cooperation to achieve common goals. Quality control: Schools must supervise the quality of food and drinks sold in school canteens. Healthy menu development: School canteens must provide healthy and nutritious menus for students.